Modulating Hox gene functions during animal body patterning. - Pearson, J.C.; Lemons, D.; McGinnis, W. (Nature Reviews. Genetics, 2005)
With their power to shape animal morphology, few genes have captured the imagination of biologists as the evolutionarily conserved members of the Hox clusters have done. Recent research has provided new insight into how Hox proteins cause morphological diversity at the organismal and evolutionary levels. Furthermore, an expanding collection of sequences that are directly regulated by Hox proteins provides information on the specificity of target-gene activation, which might allow the successful prediction of novel Hox-response genes. Finally, the recent discovery of microRNA genes within the Hox gene clusters indicates yet another level of control by Hox genes in development and evolution.